Some aspects of periodontal disease and comorbid cardiovascular diseases - D. I. Trukhan; L. Yu. Trukhan (Медицинский совет, 2015)
The article discusses the relationship between risk factors and clinical manifestations of cardiovascular disease and periodontitis.